PENGARUH PENGAWASAN BADAN PERMUSYAWARATAN DESA (BPD) TERHADAP KINERJA KEPALA DESA DALAM PEMBANGUNAN DESA RAMBAH UTAMA KECAMATAN RAMBAH SAMO KABUPATEN ROKAN HULU - Adha, Ari Hanafi; ", Ernawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
BPD as a supervisory agency has the obligation to control the implementation of village regulations, budget revenue and expenditure village (APBDes) as well as the course of the village administration. But seen from the data of rural development planned is still not fully carried out, and had been a delay in delivering the accountability report of the Chief Village Rambah Utama, because at the end of fiscal in 2014 has entered the final frontier in the third month after the fiscal year ends have not made submission of the report accountability to the Regent and BPD that should be the end of the limits set by Government Regulation No. 43 of 2014 article 49, and it seemed that the surveillance has not done.The purpose of this study was to determine whether there is a influence BPD supervision on the performance of chief village in development in the Village Rambah Utama at Rambah Samo District of Rokan Hulu and to determine how much influence BPD supervision on the performance of village heads in the construction of Village Rambah Utama. This study uses a simple regression model is based on a functional relationship or the influence of the independent variables with the dependent variable, data collection techniques by observation, interviews and questionnaires (questionnaire) to Members of BPD Officer, employe of the Village, Chief Village , Chairman of RT and RW, and community. This study uses the theory of supervision and performance by Manulang and Mangkunagara.These results indicate that the performance of the Implementation Monitoring was done by BPD on the performance of the Chief Village has with either, the recapitulation of respondents to the Control variable (variable X) with a total score of 3,442. Performance Chief Village in rural development Rambah Utama with a total score of 3,437 and supervision BPD positive also significant effect on theperformance of the Chief Village in development, it can be seen from the analysis of data obtained r value is 0.701, and of the table above shows taritmhetic> ttable where taritmhetic = 8.595 and t table = 1.984, then H0 rejected and Ha.Keywords: Performance, Monitoring. Influence